2016
DOI: 10.1038/ncomms12614
|View full text |Cite
|
Sign up to set email alerts
|

Efficient ex vivo analysis of CD4+ T-cell responses using combinatorial HLA class II tetramer staining

Abstract: MHC tetramers are an essential tool for characterizing antigen-specific CD4+ T cells. However, their ex vivo analysis is limited by the large sample requirements. Here we demonstrate a combinatorial staining approach that allows simultaneous characterization of multiple specificities to address this challenge. As proof of principle, we analyse CD4+ T-cell responses to the seasonal influenza vaccine, establishing a frequency hierarchy and examining differences in memory and activation status, lineage commitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 67 publications
1
69
0
Order By: Relevance
“…If we extrapolate the results established in mouse models of primary infection to humans, who are each likely to express at least 8–10 different HLA-class II molecules due to co-expression of different alleles and isotypes (HLA-DR, DQ and DP), as well as heterozygosity in HLA genotype (57), we anticipate that the CD4 T cell response to the initial influenza infection would encompass more than 100 different epitope specificities. This has not been tested experimentally because of the limited sampling that can take place from the peripheral blood of young children, typically 2–10 ml (58), and the relatively low frequency of CD4 T cells that are specific for single peptides, even in adults who have presumably encountered influenza multiple times (5964). …”
Section: The Specificity Of Cd4 T Cells To Influenza Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…If we extrapolate the results established in mouse models of primary infection to humans, who are each likely to express at least 8–10 different HLA-class II molecules due to co-expression of different alleles and isotypes (HLA-DR, DQ and DP), as well as heterozygosity in HLA genotype (57), we anticipate that the CD4 T cell response to the initial influenza infection would encompass more than 100 different epitope specificities. This has not been tested experimentally because of the limited sampling that can take place from the peripheral blood of young children, typically 2–10 ml (58), and the relatively low frequency of CD4 T cells that are specific for single peptides, even in adults who have presumably encountered influenza multiple times (5964). …”
Section: The Specificity Of Cd4 T Cells To Influenza Virusmentioning
confidence: 99%
“…There is a growing appreciation that vaccine strategies that more fully engage the cellular response can enhance protection. A number of recent studies have sought to quantify and characterize the repertoire of circulating memory CD4 T cells with specificity towards influenza antigens (59, 60, 62, 63, 8387). Many studies by other groups have concluded that the most prominent influenza-reactive CD4 T cells are those specific for internal virion proteins, particularly M1 and NP (8486), as well as HA (63).…”
Section: Human Memory Cd4 T Cells Reactive To Influenza Virusmentioning
confidence: 99%
“…The ability to detect and phenotype autoreactive T cells in circulation, where they are present at extremely low frequencies, has greatly improved. For example, HLA-II tetramers or HLA-I multimers/monomers allow measurement of autoreactive T cells in the circulation ex vivo, without in vitro amplification that might alter phenotypic features (8)(9)(10). This Review integrates experimental, human pathology, and clinical research studies and identifies key outstanding questions related to autoreactive T cells in T1D.…”
Section: Introductionmentioning
confidence: 99%
“…113 Furthermore, allergen-specific Tregs have been shown to expand following AIT for HDM and grass pollen allergies thereby increasing the ratio of allergen-specific Tregs over effector T cells. 32,33,114,115 To facilitate translation towards routine measurements of T-cell biomarkers, immunophenotyping approaches have been developed that only use membrane markers and allow for direct ex vivo T-cell evaluation without in vitro cell culture. The CD4+CD25+CD127phenotype specifically distinguishes human Treg, 116,117 and these cells can be quantified in allergic patients 31 with increases following SLIT for grass pollen 11 and AIT in HDM-allergic individuals.…”
Section: T Cellsmentioning
confidence: 99%
“…42,123 Many abnormalities in Treg and Th cell number and frequency have been observed within the total pool of circulating T cells, independent of antigen specificity. 30,31,42,121 With the use of MHC-peptide reagents to detect antigen specificity, 115 the sensitivity of these changes can be significantly enhanced to detect early effects of AIT. 32,113 As the application of MHC tetramers, especially for MHC class II, is limited by the diversity of alleles in the human population, there is a need for alternative markers for allergen-specific cells.…”
Section: T Cellsmentioning
confidence: 99%